منهج ابن حديدة (ت:783هـ/1381م) في كتابه " المصباح المضيء في كتاب النبي الامي ورسله الى ملوك الارض من عربي وعجمي " - رائد الراشد; محمد خليل (مجلة ابحاث كلية التربية الاساسية)
Book  of (The Bright Lamp in messages of the illiterate Prophet and His Messengers to Kings of Earth, Arabs and Non-Arabs) by Muhammad bin Alaa al-Din Ali bin Shihab al-Din al-Ansari is considered one of the historical compilations that falls alongside  Prophet’s biography. It included lineage of  Prophet (peace be upon him) , the biographies of the Rightly Guided Caliphs and their Islam. It also included letter of Prophet (peace be upon him) , his correspondents with kings of earth and their reception of delegations. This study sheds light on approach that the above mentioned author adopted in his book, This study is a step on a path taken by his ascendents, specialized in studying methods of historians, and hence came importance of this study.